Inszenierte Moderne. Populäres Theater in Berlin und London, 1880-1930 - German Historical Institute London (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2014)
Modern popular culture came to the world from the stage. Even before film and radio had established themselves, popular theater had developed into a commercial and boundary-crossing entertainment industry that reached a mass audience. Tobias Becker compares the theater landscapes of London and Berlin and points out the cultural exchanges that took place between these metropolises during the long turn of the century (1880&#82111930).